The Different Theories of Truth Three Brothers (Charles Sanders Peirce, William James and John Dewey) - Novia S. Silalahi; Avivah A. Putri; Indah K. Sianturi; Aprillia Chasanah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2019)
The theory of truth is that truth statements consist of practical consequences, especially in agreement with subsequent experience. The purpose of this study is to discuss the different theories of truth proposed by Charles Sanders Peirce, William James and John Dewey. This study uses a qualitative methodology that uses the analysis of this research article to reveal the basic theories and differences from each expert as they are known as pragmatic researchers with their theories of truth. This paper is intended to explore and provide different pragmatic theories of the three truths by Charles Sanders Peirce, William James and John Dewey. This reward research to see that results from differences in the theory of truth by Charles Sanders Peirce, William James and John Dewey which results in that Peirce is often associated with the idea that true beliefs are those who will stand the test in the future; James with the idea that true trust is reliable and also beneficial; while Dewey with that idea claims of ownership are verified (or "valuation"). Therefore, expecting further research is to find the effects of different theories of truth from the three experts in various contexts.